ChemInform Abstract: Cyclic Alkenenitriles: Copper‐Catalyzed Deconjugative α‐Alkylation. Issue 32 (22nd July 2016) - Yang, Xun; Nath, Dinesh; Morse, Jared; Ogle, Craig; Yurtoglu, Emine; Altundas, Ramazan; Fleming, Fraser
Abstract: An unusual amido cuprate, generated in situ from LDA and CuCN, is used for deprotonation of cyclic, α, β‐unsaturated nitriles.